A diaphragm for hydrogen production by alkaline electrolysis of water and a method for producing the same
Patent Information
- Application Number
- CN202510503970.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-22
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]本申请提供一种碱性电解水制氢用隔膜及其制备方法,旨在解决现有碱性电解水制氢用有机无机复合隔膜的阻气性和机械性能不足的问题
[0025]本申请的有益效果包括:本申请所述碱性电解水制氢用隔膜包含原料硅氧烷系添加剂,硅氧烷系添加剂可以和氧化锆表面的羟基发生反应,降低氧化锆的表面能,使料液体系混合的更均匀,提高料液和支撑层的结合力,同时还可提高所述隔膜对碱液的亲和性,从而达到降低面电阻的目的。
Smart Images

Figure CN122959798A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of water electrolysis for hydrogen production technology, specifically relating to a diaphragm for alkaline water electrolysis for hydrogen production and its preparation method. Background Technology
[0002] Hydrogen energy, as a secondary energy source that is abundant, green, low-carbon, and widely applicable, is gradually becoming one of the important carriers of global energy transition and development. Hydrogen is difficult to obtain directly in large quantities from nature and requires different technological pathways and production processes for its production. Currently, the main hydrogen production pathways include three types: hydrogen production from fossil fuel reforming, hydrogen production from industrial by-product gas, and hydrogen production from water electrolysis. Compared to hydrogen production from industrial by-product gas and fossil fuels, hydrogen production from water electrolysis can utilize renewable electricity generated by photovoltaic power generation, wind power, and hydropower to electrolyze water, achieving completely zero carbon emissions and green hydrogen production throughout the process.
[0003] There are four main technical routes for hydrogen production through water electrolysis: alkaline water electrolysis (AWE), proton exchange membrane water electrolysis (PEM), solid oxide electrolysis (SOEC), and anion exchange membrane water electrolysis (AEM). Currently, alkaline water electrolysis is the most mature technology, characterized by its ease of operation, low investment cost, long service life, and large-scale commercial application. The diaphragm, as a key component of alkaline water electrolysis equipment, primarily functions to prevent the mixing of hydrogen and oxygen at the anode and cathode of the electrolyzer and to facilitate the migration of electrolyte ions. Therefore, its performance determines the energy consumption, hydrogen purity, and safety of the electrolyzer under the same catalytic electrode conditions. This requires the diaphragm to have high gas barrier properties, low sheet resistance, and high mechanical strength. The organic-inorganic composite membrane for alkaline water electrolysis to produce hydrogen consists of three parts: high-molecular organic matter, inorganic nanoparticles, and supporting materials. It combines the characteristics of both organic and inorganic materials, exhibiting excellent gas barrier properties, ion permeability, alkali resistance, and mechanical properties. However, during the membrane preparation process, due to the high surface energy of nano-zirconia, it is prone to agglomeration, and its affinity with high-molecular organic matter is poor. This can lead to issues such as nanoparticle agglomeration, uneven mixing of the organic and inorganic phases, and poor bonding between the mixture and the PPS supporting material. Consequently, after curing, the membrane contains pore defects and nano-ion agglomerates, severely affecting the membrane's gas barrier properties and mechanical properties. Summary of the Invention
[0004] This application provides a membrane for alkaline water electrolysis to produce hydrogen and its preparation method, aiming to solve the problems of insufficient gas barrier properties and mechanical properties of existing organic-inorganic composite membranes for alkaline water electrolysis to produce hydrogen.
[0005] The first aspect of this application provides a diaphragm for alkaline water electrolysis to produce hydrogen, including a support layer and a feed liquid layer coated on the support layer;
[0006] The liquid layer comprises the following raw materials in parts by weight: 15-35 parts of high molecular weight organic matter, 30-60 parts of zirconium oxide, 0.01-5 parts of siloxane additives, and 20-70 parts of solvent.
[0007] According to some embodiments of the diaphragm for alkaline water electrolysis to produce hydrogen described in this application, the feed liquid layer comprises the following raw materials in parts by weight: 15-35 parts of high molecular weight organic matter, 30-60 parts of zirconium oxide, 0.5-0.8 parts of siloxane additives, and 20-70 parts of solvent.
[0008] According to some embodiments of the diaphragm for hydrogen production via alkaline water electrolysis described in this application, the siloxane-based additive includes one or more of hexaethyldisiloxane, heptamethyltrisiloxane, and 1,1,3,3,5,5,7,7,9,9,11,11,13,13,15,15-hexadecyloctasiloxane.
[0009] According to some embodiments of the diaphragm for alkaline water electrolysis to produce hydrogen described in this application, the siloxane additive is heptamethyltrisiloxane.
[0010] According to some embodiments of the diaphragm for alkaline water electrolysis to produce hydrogen described in this application, the polymeric organic material includes one or more of polysulfone, polyethersulfone, polyvinylidene fluoride, and polyphenylene sulfone.
[0011] According to some embodiments of the diaphragm for alkaline water electrolysis to produce hydrogen described in this application, the solvent includes one or more of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and N-ethylpyrrolidone.
[0012] According to some embodiments of the diaphragm for alkaline water electrolysis to produce hydrogen described in this application, the zirconium oxide has a particle size of 10-70 nm.
[0013] According to some embodiments of the diaphragm for alkaline water electrolysis to produce hydrogen described in this application, the bulk density of the zirconium oxide is 0.5-0.7 g / ml.
[0014] According to some embodiments of the diaphragm for alkaline water electrolysis to produce hydrogen described in this application, the support layer includes one or more of polyphenylene sulfide support layer, polyether ether ketone support layer and polytetrafluoroethylene support layer.
[0015] According to some embodiments of the diaphragm for alkaline water electrolysis to produce hydrogen described in this application, the thickness of the support layer is 100-300 μm, preferably 250-300 μm.
[0016] According to some embodiments of the diaphragm for alkaline water electrolysis to produce hydrogen described in this application, the mesh size of the support layer is 20-100 mesh, preferably 40-60 mesh.
[0017] The second aspect of this application provides a method for preparing the diaphragm for alkaline water electrolysis to produce hydrogen as described in the first aspect of this application, comprising the following steps:
[0018] (1) Mix the high molecular organic compound, zirconium oxide, siloxane additives and solvent to obtain a slurry;
[0019] (2) The slurry is coated onto the support layer to obtain the diaphragm for alkaline water electrolysis to produce hydrogen.
[0020] According to some embodiments of the preparation method of the diaphragm for alkaline water electrolysis to produce hydrogen described in this application, in step (1), the mixing temperature is 75-85°C and the mixing time is 24-48h.
[0021] According to some embodiments of the preparation method of the alkaline water electrolysis hydrogen production diaphragm described in this application, the preparation method further includes sequentially subjecting the support layer coated with slurry to induced phase separation, gelation, and cleaning treatment to obtain the alkaline water electrolysis hydrogen production diaphragm.
[0022] According to some embodiments of the preparation method of the diaphragm for alkaline water electrolysis to produce hydrogen described in this application, the induced phase separation treatment includes first inducing phase separation of the support layer coated with slurry in a closed environment at a temperature of 40°C and a relative humidity of 85% for 30 seconds, and then inducing phase separation in a closed environment at a temperature of 25°C and a relative humidity of 45% for 30 seconds.
[0023] According to some embodiments of the preparation method of the diaphragm for alkaline water electrolysis to produce hydrogen described in this application, the gel treatment includes immersing a support layer coated with slurry in water at 55-65°C for 8-12 minutes for gel treatment.
[0024] According to some embodiments of the method for preparing a diaphragm for alkaline water electrolysis to produce hydrogen as described in this application, the cleaning process includes washing with water at 75-85°C for 25-35 minutes.
[0025] The beneficial effects of this application include: the diaphragm for alkaline water electrolysis to produce hydrogen described in this application contains a raw material siloxane-based additive. The siloxane-based additive can react with the hydroxyl groups on the surface of zirconium oxide, reduce the surface energy of zirconium oxide, make the liquid system more uniformly mixed, improve the bonding force between the liquid and the support layer, and at the same time improve the affinity of the diaphragm for alkaline solution, thereby achieving the purpose of reducing the surface resistivity. Attached Figure Description
[0026] Figure 1 This is a scanning electron microscope image of the diaphragm for alkaline water electrolysis to produce hydrogen as described in Example 1 of this application;
[0027] Figure 2 This is a scanning electron microscope image of the diaphragm for alkaline water electrolysis to produce hydrogen as described in Comparative Example 1 of this application;
[0028] Figure 3 The above is the 1H NMR spectrum of hexaethyldisiloxane described in the embodiments of this application;
[0029] Figure 4 The above is the 1H NMR spectrum of heptamethyltrisiloxane described in the embodiments of this application;
[0030] Figure 5 The above is the 1H NMR spectrum of 1,1,3,3,5,5,7,7,9,9,11,11,13,13,15,15-hexadecyl octasiloxane described in the embodiments of this application. Detailed Implementation
[0031] The embodiments of the present invention are described in detail below. These embodiments are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0032] In this invention, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0033] This application provides a membrane for alkaline water electrolysis to produce hydrogen, comprising a support layer and a feed liquid layer coated on the support layer; the feed liquid layer comprises the following raw materials in parts by weight: 15-35 parts of high molecular weight organic matter, 30-60 parts of zirconium oxide, 0.01-5 parts of siloxane additives and 20-70 parts of solvent.
[0034] The diaphragm for alkaline water electrolysis to produce hydrogen described in this application contains a raw material siloxane-based additive. The siloxane-based additive can react with the hydroxyl groups on the surface of zirconium oxide, reducing the surface energy of zirconium oxide, making the liquid mixture more uniform, improving the bonding force between the liquid and the support layer, and also improving the affinity of the diaphragm for alkaline solution, thereby achieving the purpose of reducing surface resistivity.
[0035] In some embodiments of this application, the liquid layer comprises the following raw materials in parts by weight: 15-35 parts of high molecular weight organic compound, 30-60 parts of zirconium oxide, 0.5-0.8 parts of siloxane additive, and 20-70 parts of solvent.
[0036] In some embodiments of this application, the siloxane-based additives include one or more of hexaethyldisiloxane, heptamethyltrisiloxane, and 1,1,3,3,5,5,7,7,9,9,11,11,13,13,15,15-hexadecyloctasiloxane. The presence of siloxanes and their homologues can effectively promote the uniformity of the casting solution.
[0037] In some embodiments of this application, the siloxane-based additive is heptamethyltrisiloxane.
[0038] In some embodiments of this application, the polymeric organic compound includes one or more of polysulfone, polyethersulfone, polyvinylidene fluoride, and polyphenylsulfone.
[0039] In some embodiments of this application, the solvent includes one or more of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and N-ethylpyrrolidone.
[0040] In some embodiments of this application, the zirconium oxide has a particle size of 10-70 nm; for example, 10 nm, 20 nm, 28 nm, 33 nm, 47 nm, 53 nm, 65 nm, 70 nm, etc.
[0041] In some embodiments of this application, the bulk density of the zirconium oxide is 0.5-0.7 g / ml, such as 0.5 g / ml, 0.57 g / ml, 0.63 g / ml, 0.67 g / ml, 0.7 g / ml, etc.
[0042] In some embodiments of this application, the support layer includes one or more of polyphenylene sulfide support layer, polyether ether ketone support layer and polytetrafluoroethylene support layer.
[0043] In some embodiments of this application, the thickness of the support layer is 100-300um, such as 100um, 150um, 180um, 220um, 260um, 300um, etc.
[0044] In some embodiments of this application, the thickness of the support layer is 250-300 μm.
[0045] In some embodiments of this application, the mesh count of the support layer is 20-100 mesh, such as 20 mesh, 50 mesh, 55 mesh, 65 mesh, 78 mesh, 83 mesh, 95 mesh, 100 mesh, etc.
[0046] In some embodiments of this application, the mesh size of the support layer is 40-60 mesh.
[0047] This application also provides a method for preparing the diaphragm for alkaline water electrolysis to produce hydrogen as described in the first aspect of this application, comprising the following steps:
[0048] (1) Mix the high molecular organic compound, zirconium oxide, siloxane additives and solvent to obtain a slurry;
[0049] (2) The slurry is coated onto the support layer to obtain the diaphragm for alkaline water electrolysis to produce hydrogen.
[0050] In some embodiments of this application, in step (1), the mixing temperature is 75-85°C, such as 75°C, 78°C, 82°C, 85°C, etc., and the mixing time is 24-48h, such as 24h, 26h, 28h, etc.
[0051] In some embodiments of this application, the preparation method further includes sequentially subjecting the support layer coated with slurry to induced phase separation, gelation, and cleaning treatments to obtain the diaphragm for alkaline water electrolysis to hydrogen production.
[0052] In some embodiments of this application, the induced phase separation process includes first inducing phase separation of the support layer coated with slurry in a closed environment at a temperature of 40°C and a relative humidity of 85% for 30 seconds, and then inducing phase separation in a closed environment at a temperature of 25°C and a relative humidity of 45% for 30 seconds.
[0053] In some embodiments of this application, the gel treatment includes immersing the support layer coated with slurry in water at 55-65°C, such as 55°C, 58°C, 60°C, 62°C, 65°C, etc., for 8-12 minutes; for example, 8 minutes, 9 minutes, 10 minutes, 12 minutes, etc.
[0054] In some embodiments of this application, the cleaning process includes rinsing with water at 75-85°C for 25-35 minutes.
[0055] The technical solution of this application will be further described below with reference to specific embodiments.
[0056] The 1H NMR spectra of hexaethyldisiloxane, heptamethyltrisiloxane, and 1,1,3,3,5,5,7,7,9,9,11,11,13,13,15,15-hexamethyloctasiloxane used in the embodiments of this application are shown below. Figure 3 , Figure 4 and Figure 5 As shown.
[0057] Example 1
[0058] A method for preparing a diaphragm for alkaline water electrolysis to produce hydrogen includes the following steps:
[0059] 15 parts of polysulfone, 40 parts of zirconium oxide with a particle size of 10-30 nm and a bulk density of 0.6 g / ml, 1 part of hexaethyldisiloxane, and 46 parts of NMP were mixed at 80°C for 24 h to obtain a slurry. The slurry was coated onto both sides of a 250 μm thick, 40-mesh PPS mesh using a high-precision slit coating method. After coating, the PPS mesh coated with the slurry was placed in a sealed area at 40°C and 85% relative humidity to induce phase separation for 30 s. Then, it was removed and placed in a sealed area at 25°C and 45% relative humidity to induce phase separation for another 30 s. Subsequently, the PPS mesh was immersed in a 60°C water bath for gel treatment for 10 min, and then washed with 80°C hot water for 30 min to obtain the membrane for alkaline water electrolysis to produce hydrogen.
[0060] Example 2
[0061] The only difference between the preparation method of the diaphragm for alkaline water electrolysis to produce hydrogen described in Example 2 and that in Example 1 is that heptamethyltrisiloxane is used instead of hexaethyldisiloxane in the preparation process of the diaphragm for alkaline water electrolysis to produce hydrogen.
[0062] The specific operating steps include:
[0063] 15 parts of polysulfone, 40 parts of zirconium oxide with a particle size of 10-30 nm and a bulk density of 0.6 g / ml, 1 part of heptamethyltrisiloxane, and 46 parts of NMP were mixed at 80°C for 24 h to obtain a slurry. The slurry was coated onto both sides of a 250 μm thick, 40-mesh PPS mesh using a high-precision slit coating method. After coating, the PPS mesh coated with the slurry was placed in a sealed area at 40°C and 85% relative humidity to induce phase separation for 30 s. Then, it was removed and placed in a sealed area at 25°C and 45% relative humidity to induce phase separation for another 30 s. Subsequently, the PPS mesh was immersed in a 60°C water bath for gel treatment for 10 min, and then washed with 80°C hot water for 30 min to obtain the membrane for alkaline water electrolysis to produce hydrogen.
[0064] Example 3
[0065] The only difference between the preparation method of the membrane for alkaline water electrolysis to produce hydrogen described in Example 3 and that in Example 1 is that 1,1,3,3,5,5,7,7,9,9,11,11,13,13,15,15-hexadecylmethyloctasiloxane is used instead of hexaethyldisiloxane in the preparation process of the membrane for alkaline water electrolysis to produce hydrogen described in Example 3.
[0066] The specific operating steps include:
[0067] 15 parts of polysulfone, 40 parts of zirconium oxide with a particle size of 10-30 nm and a bulk density of 0.6 g / ml, 1 part of 1,1,3,3,5,5,7,7,9,9,11,11,13,13,15,15-hexadecylmethyloctasiloxane, and 46 parts of NMP were mixed at 80°C for 24 h to obtain a slurry. The slurry was then coated onto a 250 μm thick, 40-mesh film using a high-precision slot coating method. After coating is completed on both sides of the PPS mesh, the PPS mesh coated with slurry is placed in a closed area at 40°C and 85% relative humidity to induce phase separation for 30 seconds. Then it is taken out and placed in a closed area at 25°C and 45% relative humidity to induce phase separation for 30 seconds. Subsequently, the PPS mesh is immersed in a 60°C water bath for gel treatment for 10 minutes, and then washed with 80°C hot water for 30 minutes to obtain the membrane for alkaline water electrolysis to produce hydrogen.
[0068] Example 4
[0069] The only difference between the preparation method of the alkaline water electrolysis hydrogen production membrane in Example 4 and Example 2 is that the amount of heptamethyltrisiloxane added during the preparation of the alkaline water electrolysis hydrogen production membrane in Example 4 is different from that in Example 2.
[0070] The specific operating steps include:
[0071] 15 parts of polysulfone, 40 parts of zirconium oxide with a particle size of 10-30 nm and a bulk density of 0.6 g / ml, 0.5 parts of heptamethyltrisiloxane, and 46 parts of NMP were mixed at 80°C for 24 h to obtain a slurry. The slurry was coated onto both sides of a 250 μm thick, 40-mesh PPS mesh using a high-precision slit coating method. After coating, the PPS mesh coated with the slurry was placed in a sealed area at 40°C and 85% relative humidity to induce phase separation for 30 s. Then, it was removed and placed in a sealed area at 25°C and 45% relative humidity to induce phase separation for another 30 s. Subsequently, the PPS mesh was immersed in a 60°C water bath for gel treatment for 10 min, and then washed with 80°C hot water for 30 min to obtain the membrane for alkaline water electrolysis to produce hydrogen.
[0072] Example 5
[0073] The only difference between the preparation method of the alkaline water electrolysis hydrogen production membrane in Example 5 and Example 2 is that the amount of heptamethyltrisiloxane added during the preparation of the alkaline water electrolysis hydrogen production membrane in Example 5 is different from that in Example 2.
[0074] The specific operating steps include:
[0075] 15 parts of polysulfone, 40 parts of zirconium oxide with a particle size of 10-30 nm and a bulk density of 0.6 g / ml, 0.8 parts of heptamethyltrisiloxane, and 46 parts of NMP were mixed at 80°C for 24 h to obtain a slurry. The slurry was coated onto both sides of a 250 μm thick, 40-mesh PPS mesh using a high-precision slit coating method. After coating, the PPS mesh coated with the slurry was placed in a sealed area at 40°C and 85% relative humidity to induce phase separation for 30 s. Then, it was removed and placed in a sealed area at 25°C and 45% relative humidity to induce phase separation for another 30 s. Subsequently, the PPS mesh was immersed in a 60°C water bath for gel treatment for 10 min, and then washed with 80°C hot water for 30 min to obtain the membrane for alkaline water electrolysis to produce hydrogen.
[0076] Example 6
[0077] The only difference between the preparation method of the alkaline water electrolysis hydrogen production membrane in Example 6 and Example 2 is that the amount of heptamethyltrisiloxane added during the preparation of the alkaline water electrolysis hydrogen production membrane in Example 6 is different from that in Example 2.
[0078] The specific operating steps include:
[0079] 15 parts of polysulfone, 40 parts of zirconium oxide with a particle size of 10-30 nm and a bulk density of 0.6 g / ml, 2 parts of heptamethyltrisiloxane, and 46 parts of NMP were mixed at 80°C for 24 h to obtain a slurry. The slurry was coated onto both sides of a 250 μm thick, 40-mesh PPS mesh using a high-precision slit coating method. After coating, the PPS mesh coated with the slurry was placed in a sealed area at 40°C and 85% relative humidity to induce phase separation for 30 s. Then, it was removed and placed in a sealed area at 25°C and 45% relative humidity to induce phase separation for another 30 s. Subsequently, the PPS mesh was immersed in a 60°C water bath for gel treatment for 10 min, and then washed with 80°C hot water for 30 min to obtain the membrane for alkaline water electrolysis to produce hydrogen.
[0080] Comparative Example 1
[0081] The only difference between the preparation method of the alkaline water electrolysis hydrogen production membrane described in Comparative Example 1 and Example 2 is that no siloxane additives are added during the preparation process of the alkaline water electrolysis hydrogen production membrane described in Comparative Example 1.
[0082] The specific operating steps include:
[0083] 15 parts of polysulfone, 40 parts of zirconium oxide with a particle size of 10-30 nm and a bulk density of 0.6 g / ml, and 46 parts of NMP were mixed at 80°C for 24 h to obtain a slurry. The slurry was coated onto both sides of a 250 μm thick, 40-mesh PPS mesh using a high-precision slit coating method. After coating, the PPS mesh coated with the slurry was placed in a sealed area at 40°C and 85% relative humidity to induce phase separation for 30 s. Then, it was removed and placed in a sealed area at 25°C and 45% relative humidity to induce phase separation for another 30 s. Subsequently, the PPS mesh was immersed in a 60°C water bath for gel treatment for 10 min, and then washed with 80°C hot water for 30 min to obtain the membrane for alkaline water electrolysis to produce hydrogen.
[0084] Comparative Example 2
[0085] The only difference between the preparation method of the diaphragm for alkaline water electrolysis to produce hydrogen described in Comparative Example 2 and Example 2 is that bis-[3-(triethoxysilyl)propyl]-tetrasulfide silane coupling agent is used instead of heptamethyltrisiloxane in the preparation process of the diaphragm for alkaline water electrolysis to produce hydrogen described in Comparative Example 2.
[0086] The specific operating steps include:
[0087] 15 parts of polysulfone, 40 parts of zirconium oxide with a particle size of 10-30 nm and a bulk density of 0.6 g / ml, 1 part of bis-[3-(triethoxysilyl)propyl]-tetrasulfide silane coupling agent, and 46 parts of NMP were mixed at 80°C for 24 h to obtain a slurry. The slurry was coated onto both sides of a 250 μm thick, 40-mesh PPS mesh using a high-precision slit coating method. After coating, the PPS mesh coated with the slurry was placed in a sealed area at 40°C and 85% relative humidity to induce phase separation for 30 s. Then, it was removed and placed in a sealed area at 25°C and 45% relative humidity to induce phase separation for 30 s. Subsequently, the PPS mesh was immersed in a 60°C water bath for gel treatment for 10 min, and then washed with 80°C hot water for 30 min to obtain the membrane for alkaline water electrolysis to produce hydrogen.
[0088] Performance study of the diaphragm for alkaline water electrolysis hydrogen production described in this application.
[0089] The surface resistivity and alkali absorption rate of the alkaline water electrolysis diaphragms described in Examples 1-6 and Comparative Examples 1-2 of this application were tested in a 30% potassium hydroxide solution at 30°C. The results are shown in Table 1.
[0090] Table 1
[0091] <![CDATA[Sheet resistance (Ω·cm 2 )]]> Alkali absorption rate (%) Example 1 0.17 59 Example 2 0.15 70 Example 3 0.16 69 Example 4 0.13 86 Example 5 0.14 81 Example 6 0.19 66 Comparative Example 1 0.22 52 Comparative Example 2 0.21 63
[0092] Note: The method for testing surface resistivity is as follows: Cut the diaphragm to be tested into a 5cm × 5cm square sample, clamp the cut sample in the middle of the electrolytic cell, and secure it with a special stainless steel clamp, then connect the testing system. After placing the electrodes in the electrolytic cell, inject a 30wt% KOH solution, and measure the diaphragm surface resistivity when the solution temperature is 30℃ using an electrochemical workstation.
[0093] The method for testing alkali absorption rate is as follows: Cut the membrane to be tested into 20mm × 20mm samples, wash and soak the cut samples three times with deionized water, and then dry them thoroughly in a vacuum drying oven at 50℃. Weigh the sample to an accuracy of 0.001g, and immerse the sample in a 30% analytical grade potassium hydroxide solution for at least 4 hours. Finally, use tweezers to hold one corner of the sample and remove it from the alkali, suspend it in the air for 30 seconds, drip off the alkali solution, and weigh it on a balance. (If less than one drop of alkali solution does not drip off, press the corner of the sample containing the droplet against the container wall to make the droplet fall off before weighing). The difference between the initial and final mass is the alkali absorption rate of the membrane.
[0094] As can be seen from Table 1, the diaphragm for alkaline water electrolysis to produce hydrogen described in this application exhibits the lowest surface resistance and the highest alkali absorption rate when 0.5 parts of heptamethyltrisiloxane are added to the casting solution.
[0095] The scanning electron microscope (SEM) images of the alkaline water electrolysis hydrogen production membranes prepared in Example 1 and Comparative Example 1 of this application are shown below. Figure 1 and Figure 2 As shown.
[0096] from Figure 1 and Figure 2 As can be seen from this, the zirconium oxide contained in the alkaline water electrolysis hydrogen production diaphragm described in this application is more evenly distributed and will not fall off during the film formation process.
[0097] Although the above embodiments have been shown and described, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Any changes, modifications, substitutions and variations made to the above embodiments by those skilled in the art are within the protection scope of the present invention.
Claims
1. A diaphragm for alkaline water electrolysis to produce hydrogen, characterized in that, Includes a support layer and a liquid coating layer applied to the support layer; The liquid layer comprises the following raw materials in parts by weight: 15-35 parts of high molecular weight organic matter, 30-60 parts of zirconium oxide, 0.01-5 parts of siloxane additives, and 20-70 parts of solvent.
2. The diaphragm for alkaline water electrolysis to produce hydrogen according to claim 1, characterized in that, The liquid layer comprises the following raw materials in parts by weight: 15-35 parts of high molecular weight organic matter, 30-60 parts of zirconium oxide, 0.5-0.8 parts of siloxane additives, and 20-70 parts of solvent.
3. The diaphragm for alkaline water electrolysis to produce hydrogen according to claim 1, characterized in that, The siloxane-based additives include one or more of hexaethyldisiloxane, heptamethyltrisiloxane, and 1,1,3,3,5,5,7,7,9,9,11,11,13,13,15,15-hexamethyloctasiloxane. Preferably, the siloxane additive is heptamethyltrisiloxane.
4. The diaphragm for alkaline water electrolysis to produce hydrogen according to claim 1, characterized in that, The high molecular weight organic compound includes one or more of polysulfone, polyethersulfone, polyvinylidene fluoride, and polyphenylsulfone; And / or, the solvent includes one or more of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and N-ethylpyrrolidone.
5. The diaphragm for alkaline water electrolysis to produce hydrogen according to claim 1, characterized in that, The zirconium oxide has a particle size of 10-70 nm; And / or, the bulk density of the zirconium oxide is 0.5-0.7 g / ml.
6. The diaphragm for alkaline water electrolysis to produce hydrogen according to claim 1, characterized in that, The support layer includes one or more of polyphenylene sulfide support layer, polyether ether ketone support layer and polytetrafluoroethylene support layer.
7. The diaphragm for alkaline water electrolysis to produce hydrogen according to claim 1, characterized in that, The thickness of the support layer is 100-300 μm, preferably 250-300 μm; And / or, the mesh size of the support layer is 20-100 mesh, preferably 40-60 mesh.
8. The method for preparing the diaphragm for alkaline water electrolysis to produce hydrogen according to any one of claims 1-7, characterized in that, Includes the following steps: (1) Mix the high molecular organic compound, zirconium oxide, siloxane additives and solvent to obtain a slurry; (2) The slurry is coated onto the support layer to obtain the diaphragm for alkaline water electrolysis to produce hydrogen.
9. The method for preparing the diaphragm for alkaline water electrolysis to produce hydrogen according to claim 8, characterized in that, In step (1), the mixing temperature is 75-85℃ and the mixing time is 24-48h.
10. The method for preparing the diaphragm for alkaline water electrolysis to produce hydrogen according to claim 8, characterized in that, The preparation method further includes sequentially subjecting the support layer coated with slurry to induced phase separation, gelation, and cleaning treatments to obtain the diaphragm for alkaline water electrolysis to hydrogen production. Preferably, the induced phase separation treatment includes first inducing phase separation of the support layer coated with slurry in a closed environment at a temperature of 40°C and a relative humidity of 85% for 30 seconds, and then inducing phase separation in a closed environment at a temperature of 25°C and a relative humidity of 45% for 30 seconds. Preferably, the gel treatment includes immersing the support layer coated with slurry in water at 55-65°C for 8-12 minutes for gel treatment; Preferably, the cleaning process includes rinsing with water at 75-85°C for 25-35 minutes.